Analysis of Indonesian Crab Export Competitiveness in International Market - Riniwati, Harsuko; Harahab, Nuddin; Carla, T. Yohana (International Review of Management and Marketing, 2017)
The purpose of this research were as follows: to know and analyze the market structure and competition of Indonesian crab, comparative advantage, competitive advantage, and crab trading specialization in international market. The analytical method used were the Concentration Ratio and Herfindahl Index, Revealed Comparative Advantage (RCA), Porter Diamond Theory and Trade Specialization Index. The results showed that within 2005 - 2014 the market structure of fresh crabs in the international market was monopolistic which was lead by the moderate power of oligopoly market leader. The analysis results of Comparative Advantage Indonesian crabs during 2005 – 2014 period for fresh crabs highlighted a high advantage of RCA value of 21.43. Furthermore, the results of competitive advantage analysis of Porter Diamond Theory stated that the following items owned a high competitive strength; they were natural resources, demand conditions, the role of government and the role of opportunity. Next, the value of Trade Specialization Index for fresh crab and crab processed Indonesia obtained high specialization value of 0.99 and 0.97 respectively, on the other hand, frozen crab was still in its period of growth. It had 0.4 value. Keywords: Indonesian Crab, Concentration Ratio, Trade Specialization Index. JEL Classification: F1